(untitled) (The Review of Diabetic Studies, 2025)
Technological innovations have transformed the way Emergency Medical Technicians (EMTs) deliver pre-hospital care. This systematic review explores the integration of smart navigation systems, GPS tracking, digital mapping, real-time data sharing, and team monitoring technologies in emergency medical services (EMS). The objective is to assess how these technologies influence operational efficiency, response times, and clinical outcomes. Databases such as PubMed, Scopus, and ScienceDirect were searched for studies published between 2016 and 2025 using keywords like “EMS technology,” “real-time navigation,” and “GPS in pre-hospital care.” Findings indicate that technology-driven systems significantly reduce response times, enhance coordination between dispatch centers and field teams, and improve patient outcomes through faster intervention and better situational awareness. However, barriers such as connectivity issues, data overload, and training deficits persist. This review concludes that the integration of smart navigation and real-time data technologies is vital to modern EMS systems, with evidence supporting their role in efficiency, safety, and patient care quality. Future developments in AI and IoT will further optimize emergency response networks.